Radix of Prophetic Communicology: Ethical Perspective of the Qur'an - Asep Saeful Muhtadi (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2021)
Communication ethics has a signal footing (cue) in the ethical concepts of the Qur'an. These cues show instructions on how to build smarter and more civilized communication ethics which are more popularly called "prophetic communication". This article tries to find the argumentative radix of prophetic communication ethics in the Islamic tradition, especially the Qur'an and the Sunnah of the prophet. Text analysis and historical context are used as approaches and methods in exploring cues related to prophetic communication from Islamic tradition sources. The results show that prophetic communication cues get a foothold in the tradition of Islamic texts that can improve communication theories that develop in the West which are more oriented towards communication humanism by denying ethical and moral values which are also the natural basis of humans (sunnatullah). Several ethical concepts, such as qaul with its various conditional attributes, are revealed as evidence of these ethical cues through an interpretive approach. Likewise, its history is revealed in various forms and roles, including the role and involvement of God as an element of communicators (communicators).Keywords: prophetic communication, Qur'an ethics, qaul, and sunnah (tradition) AbstrakEtika komunikasi memiliki pijakan signal (isyarat) dalam konsep-konsep etik Qur’an. Isyarat tersebut menunjukan adanya petunjuk bagaimana membangun etika komunikasi yang lebih smart dan beradab yang lebih populer disebut ”komunikasi profetik”. Artikel ini mencoba mencari akar argumentatif etika komunikasi profetik dalam tradisi Islam, terutama Qur’an dan Sunah nabi. Analisis teks dan konteks historis digunakan sebagai pendekatan dan metode dalam menggali isyarat-isyarat terkait komunikasi profetik dari sumber-sumber tradisi Islam. Hasilnya menunjukan bahwa isyarat komunikasi profetik mendapat pijakan dalam tradisi teks Islam yang dapat memperbaiki teori-teori komunikasi yang berkembang di Barat yang lebih berorientasi pada humanisme komunikasi dengan menafikan nilai-nilai etik dan moral yang juga menjadi landasan natural manusia (sunnatullah). Beberapa konsep etik, seperti qaul dengan ragam atribut kondisionalnya diungkap sebagai bukti isyarat-isyarat etik tersebut melalui pendekatan tafsir. Begitu juga historisnya diungkap dalam ragam bentuk dan peran, termasuk peran dan keterlibatan Tuhan sebagai elemen pelaku komunikasi (komunikator).Kata kunci: Komunikasi Profetik, etik qur’an, qaul, dan Sunnah (tradisi).